Students’ use behavior towards e-learning tools during COVID-19 pandemics: Case study of higher educational institutions of Thailand - Chaiyawit Muangmee; Sebastian Kot; Nusanee Meekaewkunchorn; Nuttapon Kassakorn; Somyos Tiranawatananun; Bilal Khalid (Institute of Advanced Engineering and Science, 2021)
The research purpose was to conduct an empirical investigation into students’ use behavior of e-learning tools during the COVID-19 pandemic, a case study of higher educational institutions in Thailand. The study applied the UTAUT2 theoretical model. Primary data was collected using a structured questionnaire from a total of 1,493 students across institutions of higher learning in Thailand. Structural equation modelling (SEM) was conducted using AMOS. The findings indicated that student’s behavioral intention to use e-learning tools is positively and significantly influenced by performance expectancy (β=0.22, p<0.05); effort expectancy (β=0.14, p<0.05); social influence (β=0.20, p<0.05); facilitating condition (β=0.50, p<0.05); hedonic motivation (β=0.35, p<0.05); learning value (β=0.51, p<0.05); and social distance (β=0.46, p<0.05). Similarly, behavioral intention by the students to use e-learning tools have a positive and significant effect on actual use of e-learning tools (β=0.82, p<0.05). Learning value and social distance had the largest positive effects on the student’s behavioral intention to use e-learning tools. It is important for the higher education institutions in Thailand to consider them. They are major factors driving students towards adopting e-learning tools during disruptions as witnessed during the COVID-19 pandemic period.